2016
DOI: 10.1093/jac/dkv487
|View full text |Cite
|
Sign up to set email alerts
|

Standard susceptibility testing overlooks potent azithromycin activity and cationic peptide synergy against MDRStenotrophomonas maltophilia

Abstract: Despite lack of activity in standard MIC testing, azithromycin synergizes with cationic peptide antibiotics to kill SM in medium mimicking tissue fluid conditions. Azithromycin, alone or in combination with colistin, merits further exploration in therapy of drug-resistant SM infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 15 publications
3
50
0
Order By: Relevance
“…Intriguingly, our in vitro MIC data obtained in CA-MHB containing 44 mM NaHCO 3 was a better predictor of in vivo outcomes than the tissue culture medium, RMPI 1640. Although use of this latter medium for AST is gaining some traction as a “host mimicking milieu” [especially for Gram-negative pathogens (20, 25, 39)], we found that it falsely predicted efficacy of oxacillin and cefazolin for the in vivo treatment of some study MRSA strains, (e.g., BMC1001). Further head-to-head screening in both media, using larger MRSA strain collections, will be required to fully identify which medium is the best predictor of β-lactam efficacy in vivo against MRSA.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Intriguingly, our in vitro MIC data obtained in CA-MHB containing 44 mM NaHCO 3 was a better predictor of in vivo outcomes than the tissue culture medium, RMPI 1640. Although use of this latter medium for AST is gaining some traction as a “host mimicking milieu” [especially for Gram-negative pathogens (20, 25, 39)], we found that it falsely predicted efficacy of oxacillin and cefazolin for the in vivo treatment of some study MRSA strains, (e.g., BMC1001). Further head-to-head screening in both media, using larger MRSA strain collections, will be required to fully identify which medium is the best predictor of β-lactam efficacy in vivo against MRSA.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, several recent investigations have promoted the use of the tissue culture medium, RPMI 1640, as a more physiologic, host-mimicking media and a better predictor of in vivo susceptibility to various antimicrobials than standard growth media, especially for Gram-negative bacteria (20, 25). As opposed to our NaHCO 3 assays, we found that MICs to both β-lactams were decreased in RPMI for all five of our study strains, although the effect was somewhat less substantive for strain COL ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has also shown that certain antibiotics that have no demonstrable activity against a particular pathogen in standard laboratory minimum inhibitory concentration (MIC) testing do nevertheless sensitize the pathogen to killing by endogenous host defense peptides, such as human cathelicidin LL-37. Examples include (a) the use of the β-lactam antibiotic nafcillin against MRSA, which promotes LL-37 killing and bacterial clearance in human whole blood, in a murine necrotizing skin infection model and in human patients with recalcitrant bacteremia [47]; and (b) the use of azithromycin to sensitize highly multidrug-resistant Gram-negative bacterial pathogens such as P. aeruginosa , A. baumannii , Klebsiella pneumoniae and Stenotrophomonas maltophilia to LL-37 killing, human serum and clearance in murine models of pneumonia with each pathogen [48, 49]. …”
Section: Neutralization Of Virulence Factors: Disarming the Pathogenmentioning
confidence: 99%
“…Clinical studies have shown that azithromycin therapy can facilitate significant improvements in the lung function attributable to its anti-inflammatory action (20, 21). Combinations of azithromycin and colistin have also been shown to exhibit synergistic antibacterial action against some multidrug resistant (MDR) Gram-negative bacterial strains (22, 23). Thus, azithromycin could be a suitable candidate for combination with colistin for improved inhalation antibiotic therapy.…”
Section: Introductionmentioning
confidence: 99%